The Impact of Interest Rate Caps on the Financial Sector Evidence from Commercial Banks in Kenya - Safavian, Mehnaz (The World Bank, 2018)
Interest rate caps can have far-reaching consequences on the composition and maturity of commercial bank loans and deposits. This paper carefully documents these impacts on the formal financial sector in Kenya after the recent interest rate caps of 2016. Using bank-level panel data from before and after the caps, the paper identifies a significant decline in aggregate lending, an increase in nonperforming loans, and a change in composition of lending away from small and medium enterprises and toward safer corporate clients. Banks also shifted away from offering interest on current account deposits to preserve their interest margins. These quantitative findings are supported by qualitative evidence through detailed interviews of commercial bank executives, and have important implications for economic growth and financial inclusion